The effect of long-term left ventricular assist device support on flow-sensitive plasma microRNA levels. (15th September 2021) - Dlouha, Dana; Ivak, Peter; Netuka, Ivan; Novakova, Sarka; Konarik, Miroslav; Tucanova, Zuzana; Lanska, Vera; Hlavacek, Daniel; Wohlfahrt, Peter; Hubacek, Jaroslav A.; Pitha, Jan
Abstract: Background: Implantation of current generation left ventricular assist devices (LVADs) in the treatment of end-stage heart failure (HF), not only improves HF symptoms and end-organ perfusion, but also leads to cellular and molecular responses, presumably in response to the continuous flow generated by these devices. MicroRNAs (miRNAs) are important post-transcriptional regulators of gene expression in multiple biological processes, including the pathogenesis of HF. In our study, we examined the influence of long-term LVAD support on changes in flow-sensitive miRNAs in plasma. Materials and methods: Blood samples from patients with end-stage heart failure ( N = 33; age = 55.7 ± 11.6 years) were collected before LVAD implantation and 3, 6, 9, and 12 months after implantation. Plasma levels of the flow-sensitive miRNAs; miR-10a, miR-10b, miR-146a, miR-146b, miR-663a, miR-663b, miR-21, miR-155, and miR-126 were measured using quantitative PCR. Results: Increasing quantities of miR-126 ( P < 0.03) and miR-146a ( P < 0.02) was observed at each follow-up visit after LVAD implantation. A positive association between miR-155 and Belcaro score ( P < 0.04) and an inverse correlation between miR-126 and endothelial function, measured as the reactive hyperemia index ( P < 0.05), was observed. Conclusions: Our observations suggest that after LVAD implantation, low pulsatile flow up-regulates plasma levels of circulating flow-sensitive miRNAs, contributing to endothelial dysfunction and vascular remodeling. Highlights: Circulating miRNAs serve as important biomarkers. Low pulsatile flow upregulates mechano-sensitive miRNAs in plasma. MiRNA-126 concentration reflect the vascular dysfunction after LVAD implantation.